Performance of multiple-input multiple-output free space optics using hybrid subcarrier intensity modulation with avalanche photodiode receiver. (27th March 2019) - Giri, Rajat Kumar; Patnaik, Bijayananda
In order to improve the performance of a free space optical (FSO) communication system, hybrid pulse position modulation-binary phase shift keying-subcarrier intensity modulation (PPM-BPSK-SIM) technique is proposed. The system performance is further improved by using multiple-input multiple-output (MIMO) configuration and avalanche photodiode (APD) receiver. The use of multiple lasers and photo detectors in MIMO FSO system reduces the scintillation effect in the atmosphere. In this study, the impact of different parameters like irradiance, link distance, and turbulence level have been considered for the bit error rate (BER) analysis. The relevant mathematical model is also presented. The simulation results show that the hybrid PPM-BPSK-SIM scheme performs better compared to PPM and BPSK-SIM schemes. Also, APD receiver shows a noticeable BER improvement than p-type intrinsic n-type (PIN) receiver in our proposed scheme.